Pengaruh Luas Panen, Produksi, IKLH, PDRB, dan Penyaluran Pupuk Urea Bersubsidi terhadap Kesejahteraan Petani Jagung di Sulawesi (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to evaluate the welfare of corn farmers in Sulawesi through an analysis of the Farmer Exchange Rate (NTP), harvest area, corn production volume, Environmental Quality Index (IKLH), Gross Regional Domestic Product (PDRB), and distribution of subsidized urea fertilizer during the period 2014-2023. This study uses a quantitative approach with data obtained from official publications. The data were analyzed using a panel data regression model. The results of the analysis show that corn production, the Environmental Quality Index, and the distribution of urea fertilizer have a positive and significant effect on the Farmer Exchange Rate. Meanwhile, harvest area and Gross Regional Domestic Product have a negative and significant effect on the Farmer Exchange Rate. This shows that harvest area, production volume, Environmental Quality Index, Gross Regional Domestic Product, and subsidized urea fertilizer distribution have a significant effect on the welfare of corn farmers in Sulawesi. This study also highlights the main challenges faced by corn farmers in Sulawesi, including the impact of climate change on agricultural productivity and the lack of consistent government intervention in supporting the agricultural sector. From this research, it is hoped that the government will provide more targeted policies to improve the welfare of farmers. With the right intervention, the welfare of farmers can be significantly improved.